Effects of an art-based intervention in older adults with dementia: a randomized controlled trial - Xuefang Zhuo; Yuanjiao Yan; Rong Lin; Shuo Lin; Xiaona Zheng; Tingfang Shao; Hong Zhang; Lili Chen; Hong Li (Scientific Reports)
Abstract This study aims to evaluate the effects of a creative expressive art-based storytelling accompanied by caregivers (CrEAS-AC) program on reducing behavioral and psychological symptoms of dementia (BPSD) in older adults with dementia and caregiver burden compared to a general social contact (SC) control group. In this two-arm randomized controlled trial, dyads comprising participants with dementia and their caregivers were randomly assigned to the CrEAS-AC (n = 39) and SC groups (n = 39). Interventions were applied twice per week for 12 weeks. The primary outcomes were BPSD (NPI and AES-I) and caregiver distress, while secondary outcomes included communication ability (SFACS-S and SFACS-C), caregiver burden (CBI), and other health-related outcomes (activities of daily living and QOL-AD). All variables were measured at baseline, 12-week follow-up, and 24-week follow-up. Linear mixed model analyses indicated that participants in the CrEAS-AC group showed significantly lower scores on NPI, AES-I, caregiver distress, and CBI post-intervention at the 12-week follow-up, compared with the SC group. They also showed higher scores on QOL-AD, SFACS-S, and SFACS-C. Baseline characteristics did not modify the effects of the interventions, which were maintained until at least 24-week follow-up. The CrEAS-AC program, as an art-based intervention, is therefore potentially effective in reducing behavioral and psychological symptoms of dementia and improving communication ability and quality of life in older adults with dementia, as well as reducing caregivers’ distress and burden. Trial registration: The study was registered in the Chinese Clinical Trials Registry (ID: ChiCTR2200064838) on 19/10/2022.